2020
DOI: 10.4102/hts.v76i1.5821
|View full text |Cite|
|
Sign up to set email alerts
|

Ethics in compulsory education – Human dignity, rights and social justice in five contexts

Abstract: What children learn through their ethics and values education in school is of crucial societal relevance and is directed by school curricula. As curricula vary between countries, an international comparison is of interest. The aim of this study was to compare curricula to reveal variations in how matters of social justice were described in curricular texts, with a special focus on class, gender and race. Curricula from five different contexts were compared: Namibia; South Africa; California State, United State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
1
0
3
Order By: Relevance
“…Johansson (2020) menar dock att det är möjligt för individen att ha en uppsättning värderingar privat och en annan i arbetslivet. Läroplaner från olika länder har jämförts och slutsatsen är bland annat att den värdegrund som är inskriven i länders skiftande styrdokument påverkar den värdegrund samt de normer och värderingar som eleverna får med sig i livet (Sporre, 2020). Detta borde indikera att elever från olika delar av världen har med sig olika moraliska kompasser utifrån uppväxtlandets värdegrund, där även kulturella bakgrunder spelar in.…”
Section: Sjvd Vol 9 No 1 2024unclassified
See 2 more Smart Citations
“…Johansson (2020) menar dock att det är möjligt för individen att ha en uppsättning värderingar privat och en annan i arbetslivet. Läroplaner från olika länder har jämförts och slutsatsen är bland annat att den värdegrund som är inskriven i länders skiftande styrdokument påverkar den värdegrund samt de normer och värderingar som eleverna får med sig i livet (Sporre, 2020). Detta borde indikera att elever från olika delar av världen har med sig olika moraliska kompasser utifrån uppväxtlandets värdegrund, där även kulturella bakgrunder spelar in.…”
Section: Sjvd Vol 9 No 1 2024unclassified
“…Lvux12 ger i demokratisk anda eleverna utrymme att i diskussioner med lärarna ifrågasätta samhällets normer och värderingar (Skolverket, 2022d), ett utrymme som inte återfinns i äldreomsorgens föreskrifter eftersom det är omsorgstagaren som är centrum för värdegrunden i den praktikgemenskapen. Eftersom eleverna på VO-vux är en heterogen grupp (Skolverket, 2023e) med olika skolbakgrund är det rimligt att dra slutsatsen att eleverna har med sig skilda värdegrunder från sin skoltid i olika länder (Sporre, 2020). Om de ges möjlighet att diskutera dessa skillnader synliggörs dessa, och det blir lättare för eleverna att upptäcka och förstå de förväntade värderingarna.…”
Section: Politiskt Praktiklandskapunclassified
See 1 more Smart Citation
“…Through thematic network structures, we identified that “social justice” ( Figure 4 f) has a strong relationship with education issues (e.g., “college students”, “teacher education”, and “social work education”). The relationship between these clusters occurs because education supports ethical and moral construction in children and young people, and consequently, the social development of communities and societies [ 98 ]. The “parents” cluster appears to be related to the presence of parents in their children’s education [ 99 ], and in the relationship between parents and children, society’s expectations and the importance of parenthood and obligations towards society are found [ 100 ].…”
Section: Science Mapping Of Human Rightsmentioning
confidence: 99%